Preparation and Characterization of Citric Acid Modified Cellulose in Remediation of Acid Mine Drainage - Ambong Khalid, Sopiah; Fauziah Syed Draman1, Sarifah; Rozaimah Sheikh Abdullah, Siti; Anuar, Nornizar; ., . (International Journal of Engineering and Technology, 2018)
Limited application of pure cellulose has brought in modification to cellulose produce substances that are of renewable origin, biodegradable but have significant enhancement of their adsorption capabilities.Â In this study, cellulose was modified with citric acid and its structure was analyzed by using Fourier-Transform Infrared Spectroscopy (FTIR) spectra, Thermal Gravimetric Analysis (TGA) and Optical Microscope. FTIR results shows that there is two main important band existed in Citric Acid Modified Cellulose (CAMC) which are hydroxyl (â€“OH) band at 3345 cm-1 and carboxyl (CO) band at 1725 cm-1, while TGA study shows that the mass loss attributed by the decomposition of CAMC occur at 300ÂºC. Crystallinity and open pore structure in the microstructure of CAMC suggesting the suitability of using this CAMC in the remediation of acid mine drainage.Â Â